2004
DOI: 10.3319/tao.2004.15.4.697(a)
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Traffic Contribution to Hydrocarbons Using 2,2-Dimethylbutane as a Vehicular Indicator

Abstract: This study investigated the feasibility of using 2,2-dimethylbutane (22DMC4) as an unambiguous indicator for traffic emissions, and applied it to assess traffic contribution to individual hydrocarbons in an atmospheric environment. The concept involves using concentration ratios of individual non-methane hydrocarbons (NMHCs) to 22DMC4, which are characteristic of traffic emissions to reveal excess concentration contributed by nontraffic sources.Air samples from three collections were analyzed for 22DMC4 and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Figure 6 shows the hourly average diurnal profiles for 2,2-dimethylbutane (2,2-DMB) and acetylene before, during, and after the control. 2,2-DMB is considered a typical tracer for vehicular emissions (Chang et al, 2004), and acetylene is a tracer for vehicular and other combustion processes (Baker et al, 2008). Before the control period, the highest-/lowest-value ratios (the highest average hourly mixing ratio of one VOC species divided by the lowest average hourly mixing ratio of this species) of acetylene and 2,2-DMB were very similar with the values of 2.32 and 2.13, respectively.…”
Section: Temporal Distribution Of Ambient Vocsmentioning
confidence: 84%
See 1 more Smart Citation
“…Figure 6 shows the hourly average diurnal profiles for 2,2-dimethylbutane (2,2-DMB) and acetylene before, during, and after the control. 2,2-DMB is considered a typical tracer for vehicular emissions (Chang et al, 2004), and acetylene is a tracer for vehicular and other combustion processes (Baker et al, 2008). Before the control period, the highest-/lowest-value ratios (the highest average hourly mixing ratio of one VOC species divided by the lowest average hourly mixing ratio of this species) of acetylene and 2,2-DMB were very similar with the values of 2.32 and 2.13, respectively.…”
Section: Temporal Distribution Of Ambient Vocsmentioning
confidence: 84%
“…Tracers of industrial sources decreased most, including some halocarbons and esters. 2,2- Dimethylbutane, a tracer of motor vehicle exhaust (Chang et al, 2004), was 1 of the top 20 most decreased species.…”
Section: Mixing Ratios and Chemical Speciationmentioning
confidence: 99%
“…Factor 1 has high values of MTBE and C 5 -C 6 alkanes. MTBE is a common gasoline additive in China, and 2,2dimethylbutane is used to enhance the octane levels of gasoline (Chang et al, 2004;Song et al, 2007;Cai et al, 2010). Ethyne can be formed during fuel combustion (Blake and Rowland, 1995;Song et al, 2007;Suthawaree et al, 2010).…”
Section: Source Apportionment By Pmfmentioning
confidence: 99%
“…A recent study revealed that even in Beijing and its surrounding regions, residential use of solid fuels might be a major and underappreciated ambient pollution source for PM 2.5 (particularly black carbon, BC, and organic carbon, OC) during the winter heating period . Since substantial quantities of VOCs are released from poor-technology burning of coal and biomass/biofuels (Yokelson et al, 2008;Shrivastava et al, 2015;Fang et al, 2017;Liu et al, 2017;Cheng et al, 2018), it is of wide concern how residential use of solid fuels, particularly for wintertime household heating, would influence ambient levels and composition of VOCs. In residential areas of Izmir, Turkey, for example, household burning of coal on uncontrolled burners for domestic heating during winter was found to be a larger source of VOCs than the local traffic (Sari and Bayram, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Factor 3 contained a large amount of C6 alkanes and alkenes as well as toluene and was identified as gasoline vehicle emissions. Gasoline vehicle exhaust contains large amounts of 2,2‐dimethyl butane (Chang et al., 2004), and it was found that gasoline vehicle emissions increased the toluene content of roadsides in Guangzhou (Y. Zhang et al., 2018; Zhao et al., 2004), while the 2‐methyl pentane and 3‐methyl pentane usually emitted from motor vehicle emission (Chan et al., 2006). The high concentrations of propane, i‐butane, and n‐butane in Factor 4 suggest that it is the liquefied petroleum gas (LPG) emissions (Cai et al., 2010; Feng et al., 2020).…”
Section: Resultsmentioning
confidence: 99%